Effectiveness of Acemannan Hydrogel Administration at Concentrations of 25%, 50%, 75% Against Decrease in the Number of Macrophages in Periodontitis Rats with Diabetes Mellitus - Chandra Susanto; Susanna Halim; Gusbakti Rusip; Nada Aurelia (Postgraduate, University of Mataram, 2024)
Acemannan activity as a natural polysaccharide from Aloevera has good biodegradability and biocompatibility and has an effect on cell tissue repair. The study's objective was to ascertain whether giving Hydrogel Acemannan at concentrations of 25%, 50%, and 75% would be beneficial in lowering the quantity of macrophages in diabetic periodontitis mice . 48 white Wistar rats were used as research samples, and they were split into four groups at two different observation intervals (days 3 and 7).One-way ANOVA and posthoc LSD statistical tests were used to assess the data. The number of macrophages in each group decreased on day 7 to 3.50 ± 0.354; 2.79±0.431; 1.54 ± 0.292; 0.54 ± 0.292. The results of the one-way ANOVAX test (p≤0.05) showed that the Hydrogel Acemannan concentrations of 25%, 50%, and 75% were effective in reducing the number of macrophages in periodontitis mice with diabetes mellitus. The results of the LSD posthoc test showed that Hydrogel Acemannan concentrations of 25%, 50%, and 75% were substantially more effective than the positive control in reducing the number of macrophages in periodontal mice with diabetes mellitus (p≤0.05).